Investigations in number, data, and space / Grade 4 Penny jars and plant growth Unit 9 Patterns, functions, and change. - TERC (Firm); Pearson/Scott Foresman; Pearson Education, Inc.; Scott, Foresman and Company (Glenview, Ill. : Pearson Scott Foresman, 2008)
Part of a K-5 mathematics curriculum, with curriculum units for classroom use and resources for teachers; the Investigations curriculum was developed at TERC, formerly Technical Education Research Centers.
unit 1. Factors, multiples, and arrays : multiplication and division 1 -- unit 2. Describing the shape of the data : data analysis and probability -- unit 3. Multiple towers and division stories : multiplication and division 2 -- unit 4. Size, shape, and symmetry : 2-D geometry and measurement -- unit 5. Landmarks and large numbers : addition, subtraction, and the number system -- unit 6. Fraction cards and decimal squares : fractions and decimals -- unit 7. Moving between solids and silhouettes : 3-D geometry and measurement -- unit 8. How many packages? How many groups? : multiplication and division 3 -- unit 9. Penny jars and plant growth : patterns, functions, and change.
Resources binder contains masters and transparencies and 2 CD-ROMS (CD1: blackline masters; CD2 (Macintosh/Windows dual compatibility): LogoPaths--interactive software of geometric figures for students).
Issued in cardboard case, 29 x 26 x 32 cm.
Includes bibliographical references and indexes.
Keywords: Mathematics -- Study and teaching (Elementary); Arithmetic -- Study and teaching (Elementary)